Enhancing women's empowerment and climate-adaptive capacities in aquaculture in climate hotspots in Zambia - Mudege, N.N.; Lecoutere, E.; Arhin-Sam, K.; Kihoro, E.; Kakwasha, K.; Manyise, T. (CGIAR GENDER Impact Platform, 2025)
Aquaculture, the farming of aquatic organisms like fish, is crucial for food security, income and employment in sub-Saharan Africa. However, gender inequalities hinder women’s agency and climate-adaptive capacities in this sector. Women often face limited access to productive assets and climate-smart technologies and experience restrictive social norms. These constraints result in gendered divisions of labor, inequitable benefit distribution and disparities in resource access and power within the aquaculture value chain. Climate change affects water quality, fish health and overall production, thereby posing economic challenges to communities that rely on aquaculture and exacerbating gender inequalities.